A Radiomic MRI based Nomogram for Prediction of Heart Failure with Preserved Ejection Fraction in Systemic Lupus Erythematosus Patients: Insights From a Three‐Center Prospective Study. Issue 3 (20th January 2022) - Wu, Lian‐Ming; Shi, Ruo‐Yang; Wu, Chong‐Wen; Jiang, Meng; Guo, Qiang; Zhu, Yin‐Su; Tang, Lang‐Lang; Xu, Jian‐Rong; Pu, Jun; Zhou, Yan; Wu, Rui
Abstract : Background: Myocardial T1 and extracellular volume (ECV) fraction values have important roles in the prognostication of heart failure with preserved ejection fraction (HFpEF). However, the traditional mean quantification of intensity levels is not sufficient. Purpose: To evaluate a T1 map‐based radiomic nomogram as a long‐term prognosticator for HFpEF in systemic lupus erythematosus (SLE) patients. Study Type: Prospective. Population: A total of 115 SLE patients and 50 age‐ and gender‐matched controls. Field Strength/Sequence: A 3.0 T scanner; cine imaging, precontrast and post‐contrast T1 mapping and T2 mapping sequences. Assessment: A radiomic nomogram was developed based on precontrast T1 mapping. Three independent readers assessed and compared the ECV value and the value of the radiomic nomogram for predicting HFpEF in SLE patients. Statistical Test: Cox proportional hazard models, Youden index for determining cut‐off values for high HFpEF risk vs. low HFpEF risk classification, Kaplan–Meier analysis, intraclass correlation (ICC), and Uno C statistic test. Results: During a median follow‐up of 27 (interquartile range, 19–37) months, 31 SLE patients developed HFpEF. Patients with elevated ECV (≥31%) and a higher output (≥42.7) from the radiomic feature "S_33_sum average" of the precontrast T1 map had a significantly higher risk of developing HFpEF than those who had lower ECV (<31%) and an output <42.7. Patients with a higher "S_33_sum average" value on precontrast T1 map had a significantly increased risk for HFpEF (hazard ratio, 1.363, 95% CI, 1.130–1.645), after adjusting for covariates including ECV and LVEF. Finally, "S_33_sum average" from precontrast T1 mapping had modest but significantly incremental prognostic value over the mean ECV value (Uno C statistic comparing models, 0.860 vs. 0.835). Data Conclusion: The precontrast T1 map‐based radiomic nomogram, as a measure of diffuse myocardial fibrosis was associated with HFpEF and provided modest prognostic value for predicting HFpEF in SLE patients. Evidence Level: 1 Technical Efficacy: Stage 2